THE GROWTH OF Gmelina arborea Linn SEEDLING BY USING MICHORIZA, ENRICHMENT ORGANIC FERTILIZER AND WOOD VINEGAR - Aris Sudomo; Aditya Hani; Endah Suhaendah (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
The objective of the research to find out the influence of michoriza, enrichmeni organic fertilizer, and wood vinegar combination on growth of G. arboreaseedling. The research was conducted in the. nursery, area of Foresny Research Instiude on November 2006 to January 2007. The research used the Complete Random Design (CRD) with 6 (six) treatments. The research shows that the michoriza, enrichmentorganicfertilizer and wood vinegar combination produces 50.87 cmof the best growth of tree's height. The influence organic fertifizer in treatment combination (M1N0C0vs M1N1C0) has a significant result on growth G. arborea seedling's height. The treatment combination MINICO (44,63 cm) showed a better result than the M1N0C0 (35,55 cm). The influence of wood vinegar treatment combination has not significant result on growth G. arborea seedling's height.